Promoting activity, independence and stability in early dementia and mild cognitive impairment (PrAISED): development of an intervention for people with mild cognitive impairment and dementia - Booth, Victoria; Harwood, Rowan H.; Hood-Moore, Victoria; Bramley, Trevor; Hancox, Jennie E.; Robertson, Kate; Hall, Judith; van der Wardt, Veronika; Logan, Pip (SAGE Publishing, 2018)
This series of articles for rehabilitation in practice aims to cover a knowledge element of the rehabilitation medicine curriculum. Nevertheless, they are intended to be of interest to a multidisciplinary audience. The competency addressed in this article is an understanding of how to develop an intervention for people with mild cognitive impairment and dementia to promote their independence, stability, and physical activity